Survey of conditions for artificial aurora experiments by the second electron gyro-harmonic at EISCAT Tromsø using dynasonde data - Tsuda, T. T. (T. T.); Rietveld, M. T. (M. T.); Kosch, M. J. (M. J.); Oyama, S. (S.); Ogawa, Y. (Y.); Hosokawa, K. (K.); Nozawa, S. (S.); Kawabata, T. (T.); Mizuno, A. (A.) (Springer Nature, 2018)
Abstract We report a brief survey of matching conditions for artificial aurora optical experiments utilizing the second electron gyro-harmonic (2.7-MHz frequency) in F region heating with O-mode at the EISCAT Tromsø site using dynasonde data from 2000 to 2017. Our survey indicates the following: The possible conditions for successful artificial aurora experiments are concentrated on twilight hours in both evening and morning, compared with late night hours; the possible conditions appear in fall, winter, and spring, while there is no chance in summer, and the month-to-month variation among fall, winter, and spring is not so clear; the year-to-year variation is well correlated with the solar activity. These characteristics in the case of 2.7-MHz frequency are basically similar to those previously reported in the case of 4-MHz frequency. However, the number of days meeting the possible condition in the case of 2.7-MHz frequency is obviously large, compared with that in the case of 4-MHz frequency. In particular, unlike the 4-MHz frequency operation, the 2.7-MHz frequency operation can provide many chances for successful artificial aurora experiments even during the solar minimum.